Left Ventricular Noncompaction: A Rare Case of Nonischemic Cardiomyopathy - Tian, Julia (Case Rep Cardiol, 2019)
Isolated left ventricular noncompaction (LVNC) is a rare form of cardiomyopathy that is characterized by deep intertrabecular recesses and abnormal trabeculations that can be observed on transthoracic echocardiogram (TTE) or cardiac MRI (CMR) studies. Our case describes a 41-year-old male who presented with exertional chest pain and was discovered to have significantly reduced left ventricular ejection fraction (LVEF) which was nonischemic in etiology as confirmed by cardiac catheterization. Subsequent evaluation with CMR imaging revealed noncompaction of the left ventricle. The patient received defibrillation and lifelong anticoagulation given his elevated risk of sudden cardiac death (SCD). This case highlights the importance of considering unconventional etiologies of cardiomyopathy when investigating new-onset heart failure as well as the necessity of life-saving measures such as anticoagulation and defibrillator implantation in view of arrhythmogenic structural heart diseases.